(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Water is life, life cannot be imagined without it. Water is human and the world of animals, plants, in short, it was necessary for the whole existencea gift of nature. As science and technology progress, industrial enterprises, water in agriculture and other areas of the national economy Demand is increasing. Use of clean water in household and daily life «Water laws" (adopted in 1970).